A rare presentation of ectopic ovary in a female adolescent and the impact of obesity: a case report. (December 2016) - Agbor, Valirie; Njim, Tsi; Aminde, Leopold
Abstract Background Inguinal hernias in women of reproductive age containing the ovary are very rare. When they occur in this age group, they are mostly associated with malformations of the urogenital system. Prompt surgical intervention is the key to ensure survival of the ovary. Here we present a case of an ectopic ovary presenting like an acute appendicitis. Case presentation A 16-year-old Cameroonian girl presented at our emergency service with an acute exacerbation of a mild and intermittent right iliac fossa pain of 5 days' duration. A clinical examination revealed android obesity and signs suggestive of an acute appendicitis. An abdominopelvic ultrasound scan showed an edematous right ovary in the canal of Nuck. A prompt hernia repair was done and her postoperative period was uneventful. Conclusions An ectopic inguinal ovary remains a rare occurrence. An urgent and careful exploration of the hernia sac is the standard of care. Careful physical examination of obese girls and women is vital particularly in emergency settings, as obesity in our patient contributed greatly to a missed diagnosis. Clinicians should potentially consider the possibility of an ectopic ovary when faced with girls and women presenting with right iliac fossa pain.